The Dialectics Feminism Paradigm Of The Legal Marriage As A Form Of Legal Protection In Girls - Achmad Hariri (Syariah: Jurnal Hukum dan Pemikiran, 2021)
Abstrak: Konstitusi sebagai dasar negara memberikan petunjuk bahwa bangsa Indonesia seluruhnya memiliki hak yang sama, lihat pada pasal 27 (1) UUD 1945, termasuk posisi perempuan dan laki-laki. Namun dominasi budaya partiarki memposisikan perempuan sebagai subaltern dari laki-laki. Bagi paradigma Feminisme Legal Theory hukum merupakan produk laki-laki, sehingga menjadi barometer produk hukum adalah laki-laki, seperti penentuan upah dalam UU ketenagakerjaan,  UU terkait Lingkungan dan UU tentang perkawinan. Belakangan ada peristiwa menarik yaitu ketika Mahkamah Konstitusi mengabulkan permohonan Judicial Review terkait batas minimal usia perkawinan, dimana di UU perkawinan sebelum revisi ada perbedaan usia anak yang relatif cukup jauh, 16 tahun perempuan dan 19 laki-laki. Setelah adanya Putusan MK No. 22/Puu-Xv/2017, kemudian Pemerintah merevisi UU Nomor 1 Tahun 1974 tentang perkawinan menjadi UU No. 16 Tahun 2019 Tentang Perubahan Atas UU 1 Tahun 1974 ini mengatur batas usia untuk melakukan pekawinan, khususnya usia perempuan minimal 19 tahun bisa melakukan perkawinan, sama dengan laki. Apakah ini menandakan politik hukum Indonesia mengarah pada paradigma teori hukum feminisme atau Feminist Legal Theory (FLT). Sebenarnya masih banyak norma dalam undang undang yang bias gender, termasuk dalam UU No. 16 Tahun 2019. Adapun pendekatan dalam penelitian ini menggunakan statute approach dan conseptual approach.Kata Kunci: Paradigma Feminisme Hukum; Hukum Perkawinan; Perempuan Abstract: The constitution as the basis of the state indicates that all Indonesians have the same rights, see Article 27 (1) of the 1945 Constitution, including the position of women and men. However, the domination of patriarchal culture places women as a subaltern of men. For the paradigm of Feminist Legal Theory, the law is a product of men, so that it becomes a barometer that legal products are men, such as determining wages in labor laws, laws related to the environment, and laws on marriage. Recently, there was an interesting incident when the Constitutional Court granted the Judicial Review request related to the minimum age of marriage, wherein the Marriage Law before the revision there was a relatively different minimum age for marriage between the couples, 16 years old for girls and 19 for boys. After the Constitutional Court Decision No. 22 / Puu-Xv / 2017, then the Government revised Law No. 1 of 1974 on marriage to become Law No. 16 of 2019 concerning Amendments to Law 1 of 1974 regulates the age limit for marriage, especially women who are at least 19 years old can marry, same as men. It may indicate that Indonesian legal politics leads to the paradigm of feminist legal theory or Feminist Legal Theory (FLT). Many legal norms are gender-biased, including in Law no. 16 of 2019. The approach in this study uses a statute approach and a conceptual approach.Keywords: Legal Feminism Paradigm; Marriage Law; Women